Targeting breast cancer detection with military technology. - Irvine, J.M.
Discusses the applicability of automated target recognition technology (ATR) to early screening for breast cancer. An overview of ATR technology is given and parallels to the cancer screening problem are given. Recommendations for future investigation are given.
Keywords: Breast cancer detection targeting; Environment around target; First phase screening; Image truth; Medical diagnostic imaging; Military technology; Sensing conditions; Target conditions; Test problem characterization; Thermal imaging